The Effect of Atmosphere Perception, Perceived Value, And Hedonic Value on Consumer Loyalty Through The Service Quality of Warunk Upnormal - Resty Anugrah Kusmarini; Ujang Sumarwan; Megawati Simanjuntak (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
This study aimed to analyze the effect of the atmospheric stimulus, perceived value, and hedonic values on consumer loyalty through the service quality of Warunk Upnormal and formulate managerial implications of consumer loyalty. The study used cross-sectional data obtained from a survey using an online open-close ended questionnaire. The data were collected from 300 respondents following the criteria studied through visits of at least two times to Warunk Upnormal and the use of convenience sampling technique. The data were analyzed using Structural Equation Model (SEM) with the help of Lisrel 8.51 software. SEM was used to assess the relationship between atmospheric perception, perceived values, and hedonic values in measurements. Loyalty was analyzed using Customer Loyalty Index (CLI) to connect the factors that encourage the creation of loyalty. The results of this study indicated that atmospheric perception had a significant effect on service quality but had no effect on consumer loyalty. Value perception had a significant effect on service quality but had no effect onconsumer loyalty. Hedonic value had a significant effect on service quality but had no significant effect on consumer loyalty. Meanwhile, service quality had nosignificant effect on consumer loyalty. Keywords: atmosphere perception, consumer loyalty, hedonic value, perceived value, service quality